PILOT STUDY ON CONSUMERS’ PERCEIVED VALUES AND PURCHASE INTENTION TOWARDS SPORTSWEAR AMONG YOUTH IN PERLIS, MALAYSIA - Mohd Izzuddin Zulkifli; Mohd Sofian Mohammad Rosbi; Suraiya Ibrahim; Nur Syuhadah Kamaruddin; Nurfareena Zahari (International Journal of Accounting, Finance and Business, 2021)
Despite the recent economic downturn due to pandemic covid-19, sportswear fashion market remains as one of the most profitable industries worldwide. The growth of sales of sportswear in emerging economies is promising, which make them as the most attractive market for sportswear industry. This scenario also includes Malaysia which is one of the most attractive markets in Asian regions. This is because majority of consumers, especially youth are becoming more active in sports, along with iniatives by Ministry of Youth and Sports of Malaysia to uplift the youth to embrace sports as a lifestyle. Although sportswear fashion market is massive, little research has been conducted in regards to consumers’ perceived values and purchase intention towards sportswear. This is ironic given a large number of sportswear fashion marketers that target youth as their major consumers. This study will take an initiative to examine the influence of consumers’ perceived values on the purchase intention towards sportswear among youth in Perlis, Malaysia by adopting perceived values (PERVAL) measures. The data from a pilot survey of 35 local students in secondary schools in Perlis were gathered and analysed by using Decscriptive Analysis, Reliability Analysis and Factor Analysis